Devido processo administrativo no regime de liquidação extrajudicial - Lima, Felipe Herdem (2017)
The present work aims to discuss the obligation to iniciate a previous administrativeproceedings among all interested parties before the commecement of the special proceedingsof extrajudicial liquidation of financial institutions provided for by Law nº 6.024, de13.3.1974. In view of this, Law nº 6.024, de 13.3.1974 framework will be discussed , as wellas financial institutions officers or directors’ constitucional rights to full defense, adversaryproceedings and presumption of innocence, when they violate legal or bylaw rules.